Supervisi Akademik Kepala Sekolah SD Untuk Peningkatan Mutu Pembelajaran Pada Program Kampung Cambridge Mutiara Cendekia - Syukri Hamzah; Isnaeni Machrawinayu; Umar Diharja (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2023)
This research aims to determine the academic supervision process carried out in the implementation of the Kampung Cambridge learning program at the Mutiara Cendekia Integrated Islamic School and its impact on the quality of learning as well as follow-up plans for the results of academic supervision as part of a reflection on maintaining school quality. This research uses a qualitative descriptive method with a case study approach. This research focuses on aspects of planning, implementation and evaluation as well as identifying obstacles to the elementary school principal's academic supervision program in improving the quality of learning in the Kampung Cambridge Mutiara Cendekia program. The research steps carried out began with 1) Identifying and communicating with interested parties, 2) Collecting data, 3) Analyzing research findings, 4) Drawing conclusions. Data collection uses interview, observation and documentation methods. The results of this research found that the principal of SDIT Mutiara Cendekia Lubuklinggau planned academic supervision regularly and actively involved teachers in preparing academic supervision programs and involved students to see the assessment response to the quality of learning. School principals and teachers must have good communication and be motivators to create an interactive learning atmosphere, so training is needed that presents expert speakers to improve teacher competence. The obstacles found in this research were the lack of time for school principals, making it difficult to carry out periodic academic supervision. The solution to this obstacle is to assign senior teachers or expert teachers by involving competent deputy principals as substitutes for the principal's supervisory duties.